Water and Nitrogen Productivity of Maize under Semiarid Environments. Issue 2 (1st March 2015) - Hammad, Hafiz Mohkum; Ahmad, Ashfaq; Abbas, Farhat; Farhad, Wajid; Cordoba, Bernardo Chaves; Hoogenboom, Gerrit
ABSTRACT: Irrigated agriculture is a facing shortage of water and N in semiarid environments where these inputs are limiting factors for crop production. Experiments were conducted to optimize the water and N requirements for maize ( Zea mays L.) under semiarid environmental conditions. Crop physiological and agronomics characteristics were evaluated for three irrigation regimes and five N fertilizer levels during 2009 and 2010. The experiments were conducted in a split‐plot design by triplicating water regimes in the main plots and N levels in the subplots. Total dry matter production and crop growth rate increased with an increase in the N application rate up to 300 kg ha −1 for all irrigation regimes. In contrast, maximum grain yield was achieved with application of 250 kg N ha −1 . Polynomial analysis (third order) showed that 275 kg N ha −1 was optimum for grain yield at normal irrigation. Higher amounts of irrigation and N significantly increased water use efficiency (WUE). Since optimal N rates for maximum grain yield was 250 kg ha −1 with 525 mm irrigation water ha −1 during both growing seasons, this may be considered in formulating good agricultural practices for the soil and weather conditions resembling those of this study.